MUSLIM VOTER’S TRUST IN ISLAMIC PARTIES IN NORTH LOMBOK, NTB (2019 AND 2024) - PAUZAN BASRI (LOIS: Jurnal Hukum dan Humaniora, 2025)
This study aims to explore the behavior and trust level of Muslim voters towards Islamic parties in North Lombok Regency during the 2019-2024 period. Employing a descriptive qualitative approach, data were collected through participatory observation, in-depth interviews with religious and community leaders, election organizers, as well as from official documents and voter data to ensure validity and depth. The findings reveal that despite the Muslim majority in the region, most Muslim voters tend to support nationalist parties rather than Islamic parties in legislative elections. Key factors influencing this preference include pragmatic voter considerations focusing on party performance, candidate quality, and tangible socio-economic programs. The roles of faith-based mass organizations are significant but their loyalty often aligns with influential leaders rather than exclusively supporting Islamic parties. Additionally, the dominant influence of traditional leaders and widespread money politics contribute to the nationalist parties' electoral dominance. This voter behavior reflects a complex interaction of ideological shifts, socio-cultural dynamics, leadership structures, and economic realities. Utilizing Muhammad al-Shatibi’s contemporary Maqasid al-Shariah framework, the study interprets this phenomenon as voters prioritizing welfare and justice aligned with the overarching goals of Shariah. Islamic parties are thus urged to reform strategies by enhancing community engagement, strengthening cadre capacity, and fostering inclusive partnerships to remain competitive and build sustainable voter trust in the evolving political landscape of North Lombok.